Trastuzumab-Coated Nanoparticles Loaded With Docetaxel for Breast Cancer Therapy - Xueyan Zhang; Jiaxin Liu; Xiangyu Li; Fang Li; Robert J. Lee; Fengying Sun; Youxin Li; Zongyu Liu; Lesheng Teng (SAGE Publishing, 2019)
Docetaxel (DTX) is commonly used for breast cancer treatment. Tween 80 used for DTX dissolution in its clinical formulation causes severe hypersensitivity and other adverse reactions. In this study, trastuzumab (Tmab)-coated lipid-polymer hybrid nanoparticles (PLNs) were prepared, composed of poly ( d , l -lactide- co -glycolide), PLGA; polyethylenimine (PEI); and lipids. The PLGA/PEI/lipid formed a hydrophobic core, while Tmab was electrostatically adsorbed on the surface of the PLNs as a ligand that targets human epidermal growth factor receptor 2 (HER2)-positive breast cancer cells. The resulting PLNs, electrostatically adsorbed Tmab-bearing PLGA/PEI/lipid nanoparticles (eTmab-PPLNs), had a mean particle size of 217.4 ± 13.36 nm, a ζ potential of 0.056 ± 0.315 mV, and good stability. In vitro, the eTmab-PPLNs showed increased cytotoxicity in HER2-postive BT474 cells but not in HER2-negative MCF7 cells. Studies of the ability of eTmab-PPLNs to target HER2 were performed. The uptake of eTmab-PPLNs was shown to be dependent on HER2 expression level. Therefore, eTmab-PPLNs provide a promising therapeutic for the treatment of breast cancer.